Small-scale Experimental Testing of a Novel Marine Floating Platform with Integrated Hydro-pneumatic Energy Storage. (August 2019) - Buhagiar, Daniel; Sant, Tonio; Farrugia, Robert N.; Aquilina, Luke; Farrugia, Daniel; Strati, Federica M.
Highlights: More than 93% of the energy stored by liquid-piston compression can be recovered. Time that stored energy is held in the system has little effect on cycle performance. 60% increase in pre-charge pressure did not cause noticeable change in performance. Meteorology plays a significant role: colder seasons slightly reduce capacity. Storm data shows rapid response of internal air to sudden external temperature drop. Abstract: Co-locating energy storage within the floating platform of offshore renewable energy systems is an effective way of reducing the cost and environmental footprint of marine energy storage devices. However, the development of suitable, non-hazardous technologies, and the influence of the marine environment on their efficiency remains an open problem. Research at the University of Malta has culminated in the Floating Liquid-piston Accumulator using Seawater under Compression (FLASC) concept, a solution involving hydro-pneumatic energy storage tailored for offshore renewables. A small-scale prototype was deployed at a sheltered marine location in the Maltese Islands, in the central Mediterranean Sea. The aim of the experimental campaign was to measure the performance of the energy storage system, and to quantify the effects of different system parameters along with the surrounding meteorological conditions. Results from selected charging-discharging cycles are presented, these include different scheduling schemes and pressure ranges. Overall, results indicate that the experimental system consistently demonstrated a high thermal efficiency (> 93%) across hundreds of charging cycles. Operating pressure range and charging schedule play a limited role on the hydro-pneumatic process, whereas seasonal temperature changes play a more significant role, in that such changes can slightly alter the effective storage capacity of the system. Results from this experimental work provide a practical proof-of-concept for hydro-pneumatic marine energy storage, and can enable key conclusions to be drawn providing a basis to numerous ongoing developments in fluid-based energy storage systems for offshore implementation.